Energy in biological systems - Smith, C. A.; Wood, Edward J. (Chapman & Hall, 1991)
This series is designed for junior undergraduates and diploma students in all biological sciences, covering the field of modern biochemistry and integrating animal, plant and microbial topics. This volume focuses on the generation of biologically usable energy in living systems.